Respuestas

  • Usuario de Brainly
2014-03-03T16:23:04+01:00
2        √3      2√3         2√3
----- * ------ =---------- = ----------
√3      √3    (√3)²           3


2a        √ax      2a√ax         2a√ax        2√ax
----- * --------- =------------ =    ------------  =--------------
√ax     √ax      (√ax)²            ax              x

3 -√2        (3- √2 )      1 -√2        3 -3√3- √2 + (√2)²        3 -3√3- √2 + 2
----------- = ------------ * ------------- =  -------------------------- =    ---------------------
1 +√2        1 +√2      1 -√2                1² -(√2)²                1-2

  5 -3√3- √2
------------------    = 3√3 +√2 - 5
     -1